Chitosan-Based Layer-by-Layer Assembly: Towards Application on Quality Maintenance of Lemon Fruits - Fangyuan Chen; Jinglin Zhang; Cunkun Chen; M. G. Gloire Martha Kowaleguet; Zhaojun Ban; Lifeng Fei; Chengchen Xu (Advances in Polymer Technology)
We fabricated a novel chitosan-carboxymethyl cellulose (CMC) layer-by-layer assembly system to facilitate the postharvest quality of the fresh produce. Fourier transform infrared spectroscopy (FTIR), TA-XT2 texture analyzer, water vapor permeability (WVP) analyzer, and scanning electron microscopy (SEM) were applied to compare the properties of chitosan and layer-by-layer assembly. The strategy involved the optimization of water vapor permeability, puncture strength, and elasticity properties of multiplayer polymer coating. Results showed that the lemon (Citrus limon (L.) Burm. f.), coated by chitosan-CMC layer-by-layer assembly, displayed significantly higher lemon firmness and vitamin C content with excellent morphology, as well as inhibited weight loss and flesh browning. This study could provide support for quality maintenance in the fruit and vegetable industry and make a significant contribution to the utilization of the natural polysaccharide as a viable resource.